Development of photovoltaic module with fabricated and evaluated novel backsheet-based biocomposite materials - Abed, Alaaeddin M. H.; Salit, Mohd Sapuan; Mohamed Yusoff, Mohd Zuhri; Zainudin, Edi Syams; Al-Oqla, Faris M. (MDPI, 2019)
Photovoltaic backsheets have considerable impact on the collective performance of solar cells. Material components should withstand certain temperatures and loads while maintaining high thermal stability under various weather conditions. Solar modules must demonstrate increased reliability, adequate performance, safety, and durability throughout the course of their lifetime. This work presents a novel solar module. The module consists of an innovative polyvinylidene fluoride-short sugar palm fiber (PVDF-SSPF) composite backsheet within its structure. It was electrically and thermally evaluated. The current-voltage characteristics (I-V) were obtained using the solar module analyzer, PROVA 210PV. A thermal evaluation was accomplished using a temperature device, SDL200. The thermal test consisted of two different assessments. The first targeted the surface and backsheet of the developed module to correlate their performance from within. The second assessment compared the thermal performance of the fabricated backsheet with the conventional one. Both tests were combined into a heatmap analysis to further understand the thermal performance. Results revealed that the developed module exhibited reasonable electrical efficiency, achieving appropriate and balanced I-V curves. PVDF-SSPF backsheets proved to be thermally stable by displaying less heat absorbance and better temperature shifts. Additional research efforts are highly encouraged to investigate other characteristics. To enhance performance, further analyses are needed such as the damp heat analysis, accelerated aging analysis, and heat dissipation phenomena.